Exploring Complex Dynamics of Early Marriage in Rural Bangladesh: Reasons, Psycho-Social, Health and Economic Implications - Ahasan, Naima; Manjur, Monia; Sahota, Rupinder; Sikder, Chayon; Mia, Md Tuhin (South Asian Journal of Social Sciences and Humanities, 2025)
Early marriage remains a significant concern in rural regions of Bangladesh, making it imperative to examine the causes, psycho-social consequences, and economic impacts of early marriage. The cross-sectional study explored these complex dynamics and interviewed 400 girls/women who married before 18 in four selected districts. Descriptive and inferential statistics revealed early marriage being greatly influenced by family attitudes (62.85%) & economic pressures (42.2%). Furthermore, forcible family opinions (75.71%) with the groom’s pressure (12.85%) and love relationships (14.28%) played a major role in early marriage. Early married girls experienced depression & sadness (44%), malnutrition (42%), disrupted education (60%) and other economic challenges. Dowries impacted families massively, where 60% provided dowry by taking loans (60.37%) due to having no other option. Early-married girls faced significant hardships, enduring psycho-social and economic oppression that severely impacted their quality of life. There is a need to integrate education, awareness, and policy reforms to mitigate the far-reaching consequences of early marriage.